2021
DOI: 10.3390/ani11061794
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 70 Improves In Vitro Embryo Yield and Quality from Heat Stressed Bovine Oocytes

Abstract: Heat shock protein 70 (HSP70) is a chaperon that stabilizes unfolded or partially folded proteins, preventing inappropriate inter- and intramolecular interactions. Here, we examined the developmental competence of in vitro matured oocytes exposed to heat stress with or without HSP70. Bovine oocytes were matured for 24 h at 39 °C without (group C39) or with HSP70 (group H39) and at 41 °C for the first 6 h, followed by 16 h at 39 °C with (group H41) or without HSP70 (group C41). After insemination, zygotes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Thermotolerance in the developing embryo seems to be associated with the embryonic genome activation (8cell stage) [46], while the previous stages are exhibiting increased thermosensitivity [6,7,45,47]. In a previous study we have shown that the supplementation of in vitro maturation medium with HSP70 results in elevated thermotolerance capacity of oocytes under conditions of artificial heat stress and the effects are maintained at until the blastocysts stage [36]. Similarly, in the present study, the protective role of HSP70 was confirmed for…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Thermotolerance in the developing embryo seems to be associated with the embryonic genome activation (8cell stage) [46], while the previous stages are exhibiting increased thermosensitivity [6,7,45,47]. In a previous study we have shown that the supplementation of in vitro maturation medium with HSP70 results in elevated thermotolerance capacity of oocytes under conditions of artificial heat stress and the effects are maintained at until the blastocysts stage [36]. Similarly, in the present study, the protective role of HSP70 was confirmed for…”
Section: Discussionsupporting
confidence: 84%
“…Thermotolerance in the developing embryo seems to be associated with the embryonic genome activation (8-cell stage) [ 46 ], while the previous stages are exhibiting increased thermosensitivity [ 6 , 7 , 45 , 47 ]. In a previous study we have shown that the supplementation of in vitro maturation medium with HSP70 results in elevated thermotolerance capacity of oocytes under conditions of artificial heat stress and the effects are maintained at until the blastocysts stage [ 36 ]. Similarly, in the present study, the protective role of HSP70 was confirmed for the very early embryonic stages, as the supplementation of HSP70 in the heat stressed group showed significantly increased blastocysts yield compared to the heat stressed embryos without supplementation; however, the blastocysts yield was not restored at the levels of the C39 group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The protein encoded by HSP70 functions as a heat shock‐associated chaperone. The expression of HSP70 is considered a response mechanism that protects the embryo from the harmful effects of various sources of stress, helping to maintain cell stability and prevent apoptosis under conditions of thermal and oxidative stress (Stamperna et al., 2021). HSP70 is known to be an important inhibitor of apoptotic pathways (Lanneau et al., 2007), with its expression being upregulated to prevent apoptosis when cells encounter lethal stimuli (Stankiewicz et al., 2005).…”
Section: Discussionmentioning
confidence: 99%